2020
DOI: 10.1007/s00223-020-00708-0
|View full text |Cite
|
Sign up to set email alerts
|

Unloading-Induced Cortical Bone Loss is Exacerbated by Low-Dose Irradiation During a Simulated Deep Space Exploration Mission

Abstract: Spaceflight-induced bone losses have been reliably reproduced in Hind-Limb-Unloading (HLU) rodent models. However, a considerable knowledge gap exists regarding the effects of low-dose radiation and microgravity together. Ten-week-old male C57BL/6J mice, randomly allocated to Control (CONT), Hind-Limb Unloading (HLU), and Hind-Limb Unloading plus Irradiation (HLUIR), were acclimatized at 28 °C, close to thermoneutral temperature, for 28 days prior to the 14-day HLU protocol. HLUIR mice received a 25 mGy dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…However, Plotkin et al ( 2015 ) demonstrated that bone resorption and bone loss occur even after blocking of osteocyte apoptosis using the inhibitor of apoptosis IG9402 (bisphosphate analog that maintains osteoblast and osteocyte viability). Other studies have also demonstrated that spaceflight and HLU induced bone loss occurs even in the absence of osteocyte apoptosis (Blaber et al, 2013 ; Farley et al, 2020 ). Moreover, the results from papers reporting apoptotic osteocytes should be treated with caution because they derive from immunohistochemical analyses run on thin (5 μm) sections, potentially leading to false positives when counting empty osteocyte lacunae (Jilka et al, 2013 ).…”
Section: Secretory Signaling Proteinsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Plotkin et al ( 2015 ) demonstrated that bone resorption and bone loss occur even after blocking of osteocyte apoptosis using the inhibitor of apoptosis IG9402 (bisphosphate analog that maintains osteoblast and osteocyte viability). Other studies have also demonstrated that spaceflight and HLU induced bone loss occurs even in the absence of osteocyte apoptosis (Blaber et al, 2013 ; Farley et al, 2020 ). Moreover, the results from papers reporting apoptotic osteocytes should be treated with caution because they derive from immunohistochemical analyses run on thin (5 μm) sections, potentially leading to false positives when counting empty osteocyte lacunae (Jilka et al, 2013 ).…”
Section: Secretory Signaling Proteinsmentioning
confidence: 94%
“…Studies show that housing mice individually at 22°C results in premature cancellous bone loss which is not seen in thermoneutral conditions (28–32°C) (Patel et al, 2012 ; Iwaniec et al, 2016 ; Martin et al, 2019 ). HLU experiments that were conducted at 28–32°C showed a decrease in cancellous bone volume in distal femur in suspended mice (Keune et al, 2017 , 2019 ; Farley et al, 2020 ). Though they did not conduct the same experiments at standard temperature in parallel, their results show trabecular bone loss which is lesser than in comparable experiments at 22°C (Amblard et al, 2003 ; Lin et al, 2009 ).…”
Section: Confounding Factors and Recommendationsmentioning
confidence: 99%
“…Previous studies have shown that bone loss in astronauts is caused by apoptosis of osteocytes and increased bone resorption. [213][214][215][216] Both osteoclasts and osteoblasts can respond to mechanical stimulation in vitro. Nevertheless, the precise contributions of bone formation and resorption to microgravity-induced bone loss remain to be fully elucidated.…”
Section: Bone Remodeling Induced By Microgravitymentioning
confidence: 99%
“…The loss of bone mass has long been attributed to microgravity [73]. However, while the molecular and cellular pathways by which microgravity may act in the form of biochemical signals are still unknown, some emerging data suggest that radiation (and logically, the "bath of radiation") may also affect bones [77]. Interestingly, by radiobiologically characterizing various genetic syndromes associated with facial dysmorphy, osteoblasts were shown to be more radiosensitive than the skin of the same donor, which may suggest that IR contribution to the loss of bone mass in astronauts has been underestimated [78].…”
Section: Radiodegeneration In Spacementioning
confidence: 99%